Dry Fractionation of RBD (Refined Bleached and Deodorized) Palm Oil - Bangun P. Nusantoro (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2007)
It has been done an investigation about dry fractionation of RBD-palm oil to obtain stearin and olein fractions. Dry fractionation was conducted using a pilot plant crystallizer equipped with a high pressure filtration. Initial palm oil comprised of two major TAG, namely POP (27.88 %) and POO (24.51 %). After dry fractionation, there were accumulations of more saturated TAG in stearin fraction (POP: 31.93 %, PPP: 21.89 %). Meanwhile, more unsaturated TAG was accumulated in olein fraction (POO: 30.76%, OOO: 6.84 %). At a yield of 65 %, it was produced the olein fraction with IV: 59.7 and CP: 3.9 C. It was also found that stearin fraction had a lower iodine value (IV: 35.8) than the original palm oil (IV: 51.4) because of the accumulation of more saturated TAG. Olein fraction also showed the similar result but at the other way around. These variations of chemical composition on the palm oil and its fractions influenced their thermal behavior. The thermogram of palm oil as measured by DSC showed two melting peaks. After dry fractionation, the higher melting peak still remained in the stearin fraction (T p-stearin: 47.49 C) and the lower melting peak stayed on the olein fraction (Tp-olein: 6.01 C).ABSTRAKTelah dilakukan penelitian tentang pengolahan minyak sawit murni menjadi fraksi padat (stearin) dan fraksi cair (olein) dengan proses fraksinasi kering. Fraksinansi dilakukan menggunakan alat skala laboratorium yang terdiri dari tabung kristalisasi yang dihubungkan dengan penyaringan bertekanan. Hasil penelitian menunjukkan bahwa di dalam minyak sawit murni terkandung dua komponen utama triacylglycerol (TAG), yaitu POP (27.88%) dan POO (24.51%). Setelah dilakukan proses fraksinasi, kandungan TAG dengan derajat kejenuhan tinggi terakumulasi pada fraksi stearin (POP: 31.93%, PPP: 21.89%). Sementara itu, pada fraksi olein terakumulasi TAG dengan derajat ketidakjenuhan tinggi (POO: 30.76%, OOO: 6,84%). Pada tingkatan hasil 65%, fraksi olein yang diperoleh mempunyai nilai IV (‘iodine value’): 59.7 dan CP (‘cloud point’): 3.9 C. Angka iod dari fraksi stearin (IV: 35.8) akan lebih rendah dari minyak sawit (IV: 51.4) karena terkonsentrasinya TAG dengan derjat kejenuhan tinggi. Hal yang berkebalikan terjadi pada fraksi olein. Fakta ini memperkuat grafik dari analisa DSC, dimana dua puncak leleh pada sampel minyak sawit akhirnya terpisah menjadi masing-masing satu puncak leleh utama pada fraksi stearin dan fraksi olein. Puncak lelehpada suhu yang lebih tinggi akan merujuk pada fraksi stearin (T p-stearin: 47.49 C) sedangkan puncak leleh pada suhu yang lebih rendah akan merujuk pada fraksi olein (T p-olein: 6.01 C).